ASSESSMENT OF GREENNESS THROUGH CARBON FOOTPRINT - Dangayach, Govind Sharan; Gaurav, Gaurav; ., Jeevraj (MATTER: International Journal of Science and Technology, 2020)
With increasing global GHG emissions it is very important for global to reduce the harmful effect of GHG emissions for future generations. Since the last decade Carbon footprint has become one of the major concern for educational institutions to get their environmental impact and quantify sustainability effort. MNIT Jaipur campus is one of the technical institutes that decided to measure its carbon footprint. This research presents the maiden Carbon Footprint study of MNIT Jaipur Campus. This study was conducted using IPCC methodology with scope 1, scope 2 and scope 3. The scope 1 includes the direct transportation of campus and LPG consumptions. In scope 2, electricity was the only source of emission whereas scope 3 includes staff commuting, bore well water supply, wastewater treatment, papers, aluminum can and solid waste. The total carbon footprint of MNIT Jaipur Campus was calculated to be 1182.69 ton CO2 eq. This study concludes that 29% of the overall carbon footprint was found from purchased electricity. While emissions from LPG consumption (26%), solid waste (16%), water supply (12%) and aluminum can (10%). The activities wastewater (4%), staff commuting (1%) and direct transportation (1%) have low emission compare to other activities. GHG emission percentage from papers, staff commuting, and direct transportation are negligible. This has a great contribution to achieving carbon neutrality of the campus. The per capita average emission found to be 0.273 ton CO2 eq. per person per year. Scope 3 emission has the highest contribution to the overall emission. From the literature, it was found that very few previous studies included scope 3 for calculating the carbon footprint, but this study shows that educational institutions have a significant impact on scope 3. Therefore every institution has needed to include the entire source associated with scope 3.